Overexpression of ATP Synthase Subunit Beta (Atp2) Confers Enhanced Blast Disease Resistance in Transgenic Rice - Qiang Huang; Chunyan Chen; Xiyang Wu; Yingfei Qin; Xinqiu Tan; Deyong Zhang; Yong Liu; Wei Li; Yue Chen (Journal of Fungi, 2023)
Previous research has shown that the pathogenicity and appressorium development of Magnaporthe oryzae can be inhibited by the ATP synthase subunit beta (Atp2) present in the photosynthetic bacterium Rhodopseudomonas palustris. In the present study, transgenic plants overexpressing the ATP2 gene were generated via genetic transformation in the Zhonghua11 (ZH11) genetic background. We compared the blast resistance and immune response of ATP2-overexpressing lines and wild-type plants. The expression of the Atp2 protein and the physiology, biochemistry, and growth traits of the mutant plants were also examined. The results showed that, compared with the wild-type plant ZH11, transgenic rice plants heterologously expressing ATP2 had no significant defects in agronomic traits, but the disease lesions caused by the rice blast fungus were significantly reduced. When infected by the rice blast fungus, the transgenic rice plants exhibited stronger antioxidant enzyme activity and a greater ratio of chlorophyll a to chlorophyll b. Furthermore, the immune response was triggered stronger in transgenic rice, especially the increase in reactive oxygen species (ROS), was more strongly triggered in plants. In summary, the expression of ATP2 as an antifungal protein in rice could improve the ability of rice to resist rice blast.